2017
DOI: 10.1080/14767058.2017.1378337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on superior mesenteric artery blood flow velocities in preterm neonates

Abstract: Blood flow in SMA is significantly reduced after caffeine citrate infusion at a loading dose of 20 mg/kg. This effect continues for at least 2 h. Meanwhile, SMA BFV seems not affected by maintenance doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Although the United States Food and Drug Administration approved caffeine for apnea of prematurity, it also provided a warning that there may be a potential relationship between methyl xanthines and the development of NEC. Abdel et al found a significant decrease in the PSV and EDV and an increase in the RI of SMA blood flow after a loading dose of caffeine. These results suggested that high‐resistance intestinal blood flow may play a role in the pathogenesis of NEC …”
Section: Discussionmentioning
confidence: 98%
“…Although the United States Food and Drug Administration approved caffeine for apnea of prematurity, it also provided a warning that there may be a potential relationship between methyl xanthines and the development of NEC. Abdel et al found a significant decrease in the PSV and EDV and an increase in the RI of SMA blood flow after a loading dose of caffeine. These results suggested that high‐resistance intestinal blood flow may play a role in the pathogenesis of NEC …”
Section: Discussionmentioning
confidence: 98%
“…Soraisham et al [26] showed that a single 10 mg/kg intravenous loading dose of caffeine in preterm neonates (≤ 32 weeks' gestation) was not significantly reduced BFV in SMA. The last published study reported by Abdel Wahed et al [6] was investigated the effects of intravenous infusion of caffeine citrate at a loading dose of 20 mg/kg followed by a maintenance dose of 5-10 mg/kg/day on the SMA BFV in preterm infants (28-33 +6 weeks' gestation). The authors showed that blood flow in SMA was significantly reduced after caffeine infusion at a loading dose of 20 mg/kg, and that this effect was continued for at least two hours and improved after six hours [6].…”
Section: Discussionmentioning
confidence: 99%
“…The last published study reported by Abdel Wahed et al [6] was investigated the effects of intravenous infusion of caffeine citrate at a loading dose of 20 mg/kg followed by a maintenance dose of 5-10 mg/kg/day on the SMA BFV in preterm infants (28-33 +6 weeks' gestation). The authors showed that blood flow in SMA was significantly reduced after caffeine infusion at a loading dose of 20 mg/kg, and that this effect was continued for at least two hours and improved after six hours [6]. Soraisham et al [26] and Abdel Wahed et al [6] suggested that the effect of caffeine on intestinal blood flow might be dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations